Availability, distribution, quality and perspectives of water in Costa Rica - Ricardo Valverde (Ciencias Ambientales, 2013)
Costa Rica is a privileged country due to its rich water availability; nonetheless, the water accessibility in terms of potable quality has become more and more scarce. Such situation implies a great challenge to guarantee its current and future supply to meet water´s increasing demands for its many purposes, considering the existing disparities among the country´s geographical regions and its different users. The current paper seeks to explore this dynamics and its future perspectives under the predicted climate change scenarios.